Assessing the Potential Prognostic and Immunological Role of TK1 in Prostate Cancer - Xie, Hui; Guo, Linpei; Wang, Zhun; Peng, Shuanghe; Ma, Qianwang; Yang, Zhao; Shang, Zhiqun; Niu, Yuanjie (Frontiers in Genetics, 2022)
Background It has been reported that Thymidine kinase 1 (TK1) was up-regulated in multiple malignancies and participated in the regulation of tumor malignant behavior. However, its specific role in prostate cancer (PCa) remains unclear. Methods TK1 expression in prostate cancer patients and cell lines was identified via crossover analysis of the public datasets. A series of in vitro experiments and in vivo models were applied to investigate the function of TK1 in prostate cancer. Functional enrichment analyses were further conducted to explore the underlying mechanism. Additionally, TISIDB was applied to explore the correlation between TK1 expression and tumor-infiltrating lymphocytes, immune subtypes and immune regulatory factors. Results TK1 expression was significantly up-regulated in PCa patients and cell lines. TK1 ablation inhibited tumor cell proliferation and migration potential, and in vivo experiments showed that TK1 inactivation can significantly restrain tumor growth. Functional enrichment analysis revealed TK1-related hub genes (AURKB, CCNB2, CDC20, CDCA5, CDK1, CENPA, CENPM, KIF2C, NDC80, NUF2, PLK1, SKA1, SPC25, ZWINT), and found that TK1 was closely involved in the regulation of cell cycle. Moreover, elevated mRNA expression of TK1 was related with higher Gleason score, higher clinical stage, higher pathological stage, higher lymph node stage, shorter overall survival and disease-free survival in PCa patients. Particularly, TK1 represented attenuated expression in C3 PCa and was related with infiltration of CD4+, CD8+ T cells and dendritic cells as well as immunomodulator expression. Conclusion Our study indicates that TK1 is a prognostic predictor correlated with poor outcomes of prostate cancer patients, and for the first time represented that TK1 can promote the progression of prostate cancer. Therefore, TK1 may be a potential diagnostic and prognostic biomarker, as well as a therapeutic target for prostate cancer.